The Application of Scrotoscope-Assisted Minimally Invasive Excision for Epididymal Mass: An Initial Report - Qin, Chuying; Yang, Jinrui; Zhang, Ruochen; Yang, Yaojin; Cai, Wanghai; Li, Tao; Zhu, Qingguo; Ye, Liefu; Gao, Yunliang; Wei, Yongbao (Frontiers in Surgery, 2022)
Background: To compare the middle-term efficacy and safety results between scrotoscope-assisted (SA) minimally invasive excision and traditional open excision (OE) for the treatment of epididymal mass. Methods: A total of 253 males with surgery excision of epididymal mass from 2012 to 2018 were included in this retrospective study. Patients were divided into two groups: traditional OE group and SA group. Patient demographics, intraoperative and postoperative outcomes were obtained and compared between these two groups. Results: 174 patients (68.8%) underwent SA and other 79 (31.2%) underwent OE. Demographic data was similar between the two groups. Compared with OE surgery, SA could significantly shorten operating time (19.4±4.1 vs 53.8±12.9 minutes), reduce blood loss (5.3±1.5 vs 21.3±5.6 mL) and downsize the operative incision (1.5±0.3 vs 4.5±0.8 cm). Additionally, postoperative complications were significantly less occurred in SA group than those in OE (15.5 % vs 21.5%), in particular scrotal hematoma (1.7% vs 12.7%) and incision discomfort (2.8% vs 6.3%). Patients in SA group had a significant higher overall satisfaction score (94.8±3.7 vs 91.7±4.9) and a significant shorter length of hospital stay (4.1±0.9 vs 5.0±1.5 days) than those in OE group. No postoperative testicular atrophy occurred in SA group. Conclusion: SA is emerging as a novel and effective option with promising perspectives for epididymal mass therapy.